Climate and land-use changes coupled with low coverage of protected areas threaten palm species in South Brazilian grasslands - Calambás Trochez, Licet Fernanda (2021)
South Brazilian grasslands are at risk due to climate change and activities that convert native vegetation into agricultural lands. We used 12 native palm species as ecological indicators of these ecosystems to evaluate the impact of climate and land-use changes on their geographical distribution. We estimated the potential distribution of species for current and future (year 2050; RCP 4.5 and 8.5) climate and land-use conditions considering two dispersal scenarios. We also assessed the coverage of protected areas (PAs) for current and future species distribution. Our results indicated that the future distribution of all species will decrease under scenarios with no dispersal and increase under scenarios with dispersal; however, a dispersal scenario might be unlikely considering species dispersal ability and the increased pressure on grasslands. A comprehensive strategy is fundamental to ensure species conservation and recovery since the current PAs network covers less than 2% of the current distribution for nine out of the 12 species. Assessing the synergy of trends in climate and land-use changes is essential to improve conservation strategies for these emblematic species.